2008
DOI: 10.1016/j.ejvs.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Great Saphenous Vein Sclerotherapy Using Standardised Polidocanol Foam (ESAF): A Randomised Controlled Multicentre Clinical Trial

Abstract: Standardised 3% polidocanol foam is more efficient and equally safe compared to 3% liquid polidocanol for treatment of GSV. In comparison to other studies a relatively small volume was injected into relatively large veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
22

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 19 publications
1
118
0
22
Order By: Relevance
“…39 121 reported more haematoma events in the LS group than in the FS group. Lurie et al 42 reported significantly fewer cases of haematoma in the RFA group than in the surgery group at each follow-up (3 days, 1 week and 3 weeks; p < 0.05 for all time points).…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 91%
See 3 more Smart Citations
“…39 121 reported more haematoma events in the LS group than in the FS group. Lurie et al 42 reported significantly fewer cases of haematoma in the RFA group than in the surgery group at each follow-up (3 days, 1 week and 3 weeks; p < 0.05 for all time points).…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 91%
“…Only three trials [119][120][121] included LS as a comparator (with FS) (see Table 8). The principal common comparator was therefore surgery (i.e.…”
Section: Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many works providing good results about the use of POL foam sclerotherapy (Alos et al, 2006;Cabrera et al, 2000;Cavezzi and Frullini, 1999;Frullini, 2000;Gachet, 2001;Garcia-Mingo, 1999;Hsu and Weiss, 2003;Ouvry et al, 2008;Rabe et al, 2008;Redondo and Cabrera, 2005;Santos, 2008;Tessari, 2000). The ability to be agitated and foamed increases the potency of detergents from 2 to 4 times by mechanically displacing blood and thus maximizing surface area and time in contact with endothelium.…”
Section: Foaming Processmentioning
confidence: 99%